Bartonella henselae infection induces a persistent mechanical hypersensitivity in mice - Vieira-Damiani, Gislaine (Rev Inst Med Trop Sao Paulo, 2020)
Bartonella spp. are re-emerging and neglected bacterial pathogens. The natural reservoirs for several species of this genus are domestic animals such as cats and dogs, the most common pets in the USA and Brazil. Some cat studies suggest that the infection is more prevalent in tropical and poverty-stricken areas. These bacteria were associated with a wide spectrum of clinical manifestations: fever of unknown origin, endocarditis, angiomatosis, chronic lymphadenopathy, hepatitis, fatigue, paresthesia and pain. Our group has already demonstrated that B. henselae -infected sickle cell disease mice present with hyperalgesia. We hypothesized that even immunocompetent mice infected by B. henselae would show an increased and persistent mechanical sensitivity. Five ten-week old male BALB/c mice were intraperitoneally inoculated with a 30 µL of suspension containing 10 (4) CFU/mL of B. henselae, while five others were inoculated with an equal volume of saline solution. Four days after bacterial inoculation, the mechanical paw withdrawal threshold was measured using von Frey filaments in all animals, for five consecutive days. The infected animals showed hypersensitivity to mechanical stimuli for five consecutive days. The present study has demonstrated that B. henselae infection induces persistent mechanical hypersensitivity, a signal consistent with pain.